STRATEGI PELAYANAN APLIKASI MOBILE PEGADAIANSYARIAH DIGITAL (PSD) DI KANTOR PEGADAIAN SYARIAH - Sudiah Hestianah; Dian Mafulla; Dedeh Imam Fatmasari (Sekolah Tinggi Ilmu Ekonomi Darul Falah Mojokerto, 2021)
This study aims to determine the extent of the business strategy of the DigitalSharia Pawnshop (PSD) application service in supporting transactions andoptimizing the potential and opportunities that exist in the face of competition.This research method uses descriptive qualitative research. The discussion ofresearch results using a descriptive approach. From the results of this study, itshows that with the implementation of a mobile application, it is very easy forthe public to make transactions at the Sharia Pawnshop. So that the Digital ShariaPawnshop (PSD) in this case sharpens the unique value or differentiation of thecompany in the face of competition.